Crucial role of T cells in NAFLD-related disease: A review and prospect - Mao, Tianyu; Yang, Rui; Luo, Yi; He, Kang (Frontiers in Endocrinology, 2022)
Nonalcoholic fatty liver disease (NAFLD) includes a series of hepatic manifestations, starting with liver steatosis and potentially evolving towards nonalcoholic steatohepatitis (NASH), fibrosis, cirrhosis or even hepatocellular carcinoma (HCC). Its incidence is increasing worldwide. Several factors including metabolic dysfunction, oxidative stress, lipotoxicity contribute to the liver inflammation. Several immune cell-mediated inflammatory processes are involved in NAFLD in which T cells play a crucial part in the progression of the disease. In this review, we focus on the role of different subsets of both conventional and unconventional T cells in pathogenesis of NAFLD. Factors regarding inflammation and potential therapeutic approaches targeting immune cells in NASH are also discussed.